2018
DOI: 10.1007/s12550-018-0333-2
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemical detection of mycotoxins in donkey milk

Abstract: The applicability of enzyme immunoassays (EIA) for aflatoxin M1 (AFM1), ochratoxin A (OTA) and zearalenone (ZEN) to analyse these toxins in donkey milk (Equus asinus) was studied. For AFM1 and OTA analysis, milk could be analysed by EIA without sample pretreatment. For ZEN, heat treatment at 78 °C for 30 min prior EIA analysis was required to avoid false positives. To include detection of phase II metabolites of ZEN, samples were additionally treated with glucuronidase/sulfatase for this EIA. Detection limits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
5
1
Order By: Relevance
“…Presently, no data are available concerning the OTA half-life in equine species. The occurrence of OTA in milk samples collected from jennies in this study was in disagreement with the results reported by Gross et al [18], probably due to the different analytical determination used (ELISA with respect to HPLC) and to the low number of milk samples (n = 6). In our study, continuous monitoring of donkey milk has allowed to show the presence of OTA in the blood and milk probably due to a batch of hay of poor quality and containing OTA.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Presently, no data are available concerning the OTA half-life in equine species. The occurrence of OTA in milk samples collected from jennies in this study was in disagreement with the results reported by Gross et al [18], probably due to the different analytical determination used (ELISA with respect to HPLC) and to the low number of milk samples (n = 6). In our study, continuous monitoring of donkey milk has allowed to show the presence of OTA in the blood and milk probably due to a batch of hay of poor quality and containing OTA.…”
Section: Discussioncontrasting
confidence: 99%
“…Table 1 shows the OTA levels found in feed samples that were grouped into three major groups according to the level of OTA contamination. The incidence of positive feed samples was very low (32%); OTA concentrations found in feed samples ranged from 0.3 to 2.7 ng/g, were far below the guidance OTA values in feed materials (cereals and cereal-based products), and composed feeds for pigs, poultry, cats, and dogs reported by the Commission Recommendation 2006/576/EC [18]. The analysis of each cereal component present in the feed showed similarly low OTA levels (0.15-0.18 ng/g) in bran, corn flake, and soy, whereas barley and oat were uncontaminated (detection limit of 0.1 ng/g).…”
Section: Ota Contamination In Feedmentioning
confidence: 84%
See 1 more Smart Citation
“…According to the authors, these data can be due to the type of feed (the animals were reared on pasture), and to the very low carry-over of aflatoxin B 1 to M 1 that has been reported for donkeys [ 76 ]. Finally, also in the case of the study carried out in Germany, the authors suggest that the absence of AFM 1 in the milk samples can be explained by the feeding of the animals that consisted of grass and hay, supplemented by pelleted feed and oat grains, which were tested negative for AFB 1 [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, processing temperatures also decrease OTA in milk. For example, Turkey-based research on raw milk, pasteurized and ultra-high temperature (UHT) milk samples contained OTA of 137 ± 57 ng/L, 135 ± 8 ng/L, and 85 ± 4 ng/L, respectively ( Gross et al., 2019 ). However, donkey milk samples showed the absence of OTA, even though the feed samples were contaminated with ≤4 μg/kg of OTA ( Boudra et al., 2013 ).…”
Section: Contamination Of Ota In the Feed Of Meat-producing Animalsmentioning
confidence: 99%